A Whitman chronology - Krieg, Joann P. (University of Iowa Press, 1998)
All Whitman scholars have encountered the frustration of trying to track down an event in Whitman's life - the last time he saw Peter Doyle, when he moved to his own home on Mickle Street in Camden, when he met Oscar Wilde. The records of these events in Whitman's long life are buried in seven volumes of his abundant correspondence, in nine volumes of his conversations with Horace Traubel, in nine volumes of his notebooks and manuscripts, and in countless writings produced by his friends and admirers. To fulfill a long-felt need for order among this embarrassment of riches, Joann K.